Uptake studies in rat Peyer's patches, cytotoxicity and release studies of alginate coated chitosan nanoparticles for mucosal vaccination - Borges, Olga (2006)
The design of particulate vaccine delivery systems, particularly for mucosal surfaces, has been a focus of interest in recent years. In this context, we have previously described the development and the characterization of a new nanosized delivery system, consisting of a model antigen adsorbed to chitosan particles and coated with sodium alginate. In the present work the ovalbumin release profiles from these coated nanoparticles in different pH buffers were investigated and compared to those of the uncoated particles. Cytotoxicity of the polymers and nanoparticles was assessed using the MTT assay. Finally, particle uptake studies in rat Peyer's patches were performed. It was demonstrated that the coating of the nanoparticles with sodium alginate not only avoided a burst release observed with uncoated particles but also increased the stability of the particles at pH 6.8 and 7.4 at 37 °C. At neutral pH, the release was lower than 5% after 3.5 h incubation in a low ionic strength buffer. For both, chitosan and alginate polymers, and for the nanoparticles, comparable cell viability data close to 100%, were obtained. Additionally, based on confocal laser scanning microscopy observations, it was shown that alginate coated nanoparticles were able to be taken up by rat Peyer's patches, rendering them suitable carriers for intestinal mucosal vaccination.